Comparison of the effects of hamstring stretching using proprioceptive neuromuscular facilitation with prior application of cryotherapy or ultrasound therapy - Arlindo Rodrigues de Mesquita Junior; Orsini, Marco; Rodrigues, Ezaine Costa; Victor Hugo do Vale Bastos; Rayele Pricila Moreira dos Santos; Guilherme Pertinni de Morais Gouveia; Dionis de Castro Dutra Machado; Magalhães, Francisco Elezier Xavier; Harnold’s Tyson de Sousa Meneses; Gouveia, Samara Sousa Vasconcelos (Journal of Physical Therapy Science, 2015)
[Purpose] Stretching using proprioceptive neuromuscular facilitation involve physiological reflex mechanisms through submaximal contraction of agonists which activate Golgi organ, promoting the relaxation reflex. The aim of this study was to evaluate the effects of proprioceptive neuromuscular facilitation alone and with prior application of cryotherapy and thermotherapy on hamstring stretching. [Subjects and Methods] The sample comprised of 32 young subjects with hamstring retraction of the right limb. The subjects were randomly allocated to four groups: the control, flexibility PNF, flexibility PNF associated with cryotherapy, flexibility PNF in association with ultrasound therapy. [Results] After 12 stretching sessions, experimental groups showed significant improvements compared to the control group. Moreover, we did not find any significant differences among the experimental groups indicating PNF stretching alone elicits similar results to PNF stretching with prior administration of cryotherapy or thermotherapy. [Conclusion] PNF without other therapy may be a more practical and less expensive choice for clinical care.